Moscow's Heavy Shadow : The Violent Collapse of the USSR - Scarborough, Isaac McKean (Book collections on Project MUSE., 2023)
"This book describes the collapse of the Soviet Union from the perspective of Tajikistan, emphasizing the violence and economic degradation endemic in the final years of the USSR (1985-1991)"--